(untitled) (Materiali di Estetica. Terza serie, 2021)
Leonardo Mosso architectural research is marked by a true love for the structure meant as generator of a transformation system. The constant elaboration of an architectural design theory will remain the founding premise of an interest in semiology. Promoting the method of a programmed architecture, Mosso makes his practice unique: utopian in the development of possibilities of construction.